Evaluación técnico financiera de un sistema de transmisión lubricado para bombas de cavidades progresivas para un pozo productor del campo La Cira Infantas (2018)
This thesis was carried out in conjunction with the International Company Occidental de Colombia LLC. For its development, first, a description of the geological generalities belonging to the field of interest was made, which on this occasion was La Cira Infantas, located in the Middle Valley Basin of Magdalena, then, is spoken in a general way about the types of recovery that exist in the industry and on the artificial lift systems that are used in the field. Likewise, emphasis is placed on the lifting system of interest (Progressive Cavitie Pump), on the use of hollow rod or pipeline and the problems associated with it.